Gerakan Perlawanan Masyarakat Pegunungan Rembang Terhadap Pembangunan Pabrik Semen Indonesia Pada Tahun 2014-2017 - Galih Satria Pangayom; Nur Hidayat Sardini; Puji Astuti (Journal of Politic and Government Studies, 2017)
The development of social movement is increasingly widespread and more complex,especially in Indonesia. Social movement often arise because there is a injustice anddisagreement between one party with another party. That is same way with the resistance ofPegunungan Kendeng society againts Semen Indonesia project in Rembang. The rejectionbased on villagers worried to the impact of factory construction. The purpose of thisresearch is to know the dynamics and the factors that encourage the resistance movement.The research method used in this research is qualitative research method with datacollection technique that is interview, literature study, and documentation. The selectedinformer were actor and Gunem subdistricts society who affected by the construction.The result of this research shown that the dynamics of social movement in Rembang iscomplex and through the stages, start from pra condition stages, legal path stages, postSupreme Court decision stages. Beside that before doing the action, they discuss what wouldthey do during the action.The recommendation that researcher can give to Government and Investors are TheGoverment should be firm when making regulations and should be obey the rule. In otherhand, investor, especially PT Semen Indonesia should invite villagers who affected bycontsruction to their development planning.Keywords: Social Movements, Pegunungan Kendeng